Research progress on detection methods for hepatitis B virus covalently closed circular DNA. Issue 5 (18th February 2023) - Sun, Fenglan; Xia, Wei; Ouyang, Yaoling
Abstract: Hepatitis B virus (HBV) infection remains a serious global public health problem, and HBV covalently closed circular DNA (cccDNA) in the nucleus of infected cells cannot be eliminated by current treatments and is a major factor in the persistence and recurrence of hepatitis B. Efficient and scientific detection methods are important for clinical monitoring of cccDNA and targeted drug development. Western blotting is the gold standard for the quantitative detection of cccDNA, but it is time‐consuming and complex. In recent years, new detection technologies have been continuously updated. There are new developments and breakthroughs in both next‐generation polymerase chain reaction (PCR) and non‐PCR methods such as in situ hybridization. Some HBV‐related markers (such as hepatitis B core‐related antigen) have also been shown to be closely related to cccDNA, and they can be used as surrogate markers to indirectly reflect cccDNA content. In this paper, the main detection methods of cccDNA and their improvements are reviewed, the advantages and limitations of these methods are analysed and summarized, and future development directions are proposed.